Professional burnout among physicians and nurses in Asian intensive care units: a multinational survey - Kay Choong See (2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature and ESICM. Purpose: Professional burnout is a multidimensional syndrome comprising emotional exhaustion, depersonalization, and diminished sense of personal accomplishment, and is associated with poor staff health and decreased quality of medical care. We investigated burnout prevalence and its associated risk factors among Asian intensive care unit (ICU) physicians and nurses. Methods: We conducted a cross-sectional survey of 159 ICUs in 16 Asian countries and regions. The main outcome measure was burnout as assessed by the Maslach Burnout Inventory-Human Services Survey. Multivariate random effects logistic regression analyses of predictors for physician and nurse burnout were performed. Results: A total of 992 ICU physicians (response rate 76.5%) and 3100 ICU nurses (response rate 63.3%) were studied. Both physicians and nurses had high levels of burnout (50.3% versus 52.0%, P = 0.362). Among countries or regions, burnout rates ranged from 34.6 to 61.5%. Among physicians, religiosity (i.e. having a religious background or belief), years of working in the current department, shift work (versus no shift work) and number of stay-home night calls had a protective effect (negative association) against burnout, while work days per month had a harmful effect (positive association). Among nurses, religiosity and better work-life balance had a protective effect against burnout, while having a bachelor’s degree (compared to having a non-degree qualification) had a harmful effect. Conclusions: A large proportion of Asian ICU physicians and nurses experience professional burnout. Our study results suggest that individual-level interventions could include religious/spiritual practice, and organizational-level interventions could include employing shift-based coverage, stay-home night calls, and regulating the number of work days per month.